Soil Improvement and Embankment Stability Using A Combination of Preloading and Prefabricated Vertical Drain (PVD) - Fatmawati, Risma Eka; Putra, Paksitya Purnama; Nurtjahjaningtyas, Indra (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
The construction of Double Track Sepanjang-Mojokerto KM 48 + 800 to KM.48 + 950 passes through an area with soft and compressible subgrade soil known from field testing data. After analyzing and calculating the settlement value, high settlement value is obtained for a long period. Efforts to solve the settlement problem in this study are to accelerate the settlement time using the Prefabricated Vertical Drain combined with Preloading. The use of this method aims to accelerate the process of settlement in the soil and increase the value of the soil shear strength (Cu) so that the subgrade becomes more stable also utilizes the pressure from the embankment, which also functions as a load (surcharge) that has been adjusted to traffic and construction loads. PVDs were installed with different patterns and spacing variations in order to calculate the efficiency of installation. Based on consideration of the number and time of PVDs to achieve 90% consolidation, a rectangular installation pattern with a spacing of 1.5 meters was selected, which was installed as thick as compressible soil layer at each point. The PVD calculation used settlement data obtained from the sum of consolidation settlement (SC) and immediate settlement (SI) from variations in the height of the embankment depicted in graphical form, which resulted in a polynomial equation. From this equation, the backfill requirement used to achieve the planned elevation of the embankment after the subgrade was installed with PVDs was obtained. Subgrade backfilling was carried out with a planned embankment height of 9-10 meters. The calculation was continued to find the increase in Cu of the subgrade and then analyzed for stability using the Geoslope program. The results of the final stability analysis after the soil improvement method at the point under review ranged from 1.8 to 1.98 and it was safe.